Muted voices: The unexplored sexuality of young persons with learning disability in Malta. - Azzopardi Lane, Claire L.; Cambridge, Paul; Murphy, Glynis (British Journal of Learning Disabilities, 2019)
Accessible summary: Persons with learning disability who live in Malta, especially women, feel they do not have as many opportunities to make friends and form relationships as other persons who do not have a learning disability.Persons with learning disability feel lonely but wish they had the opportunity to do the things non‐disabled people do, such as have relationships, get married, live on their own and have children.At times, their parents and people who work with them do not help them with this.It is important that persons with learning disability from a young age are supported and empowered so that they can exercise their sexual rights. Background: This paper explores the sexuality of young persons with learning disability in Malta with respect to their opportunities and the constraints they experience. Materials and Methods: Interpretative phenomenological analysis was used to decode qualitative data collected from persons with learning disability. Results: Findings reveal a context of disabling social attitudes, stereotypical gender imagery and exclusionary social practices. In addition, youth with learning disability experience a lack of community support and social networking, thus calling for platforms and spheres where they can form and maintain friendships and relationships. Conclusions: It is concluded that Malta lacks the fundamental social acceptance that persons with learning disability are sexual beings, with the right to express their sexuality and to form relationships. Overcoming such cultural hurdles will empower persons with learning disability to establish and express their sexual identities.